Perioperative and anesthesia-related cardiac arrests in geriatric patients: A systematic review using meta-regression analysis - Braghiroli, Karen S. [UNESP]; Braz, José R. C. [UNESP]; Rocha, Bruna [UNESP]; El Dib, Regina [UNESP]; Corrente, José E. [UNESP]; Braz, Mariana Gobbo [UNESP]; Braz, Leandro Gobbo [UNESP] (Springer Nature, 2017)
The worldwide population is aging, and the number of surgeries performed in geriatric patients is increasing. This systematic review evaluated anesthetic procedures to assess global data on perioperative and anesthesia-related cardiac arrest (CA) rates in geriatric surgical patients. Available data on perioperative and anesthesia-related CA rates over time and by the country's Human Development Index (HDI) were evaluated by meta-regression, and a pooled analysis of proportions was used to compare perioperative and anesthesia-related CA rates by HDI and time period. The meta-regression showed that perioperative CA rates did not change significantly over time or by HDI, whereas anesthesia-related CA rates decreased over time (P = 0.04) and in high-HDI (P = 0.015). Perioperative and anesthesia-related CA rates per 10,000 anesthetic procedures declined in high-HDI, from 38.6 before the 1990s to 7.7 from 1990-2017 (P < 0.001) and from 9.2 before the 1990s to 1.3 from 1990-2017 (P < 0.001), respectively. The perioperative CA rate from 1990-2017 was higher in low-HDI than in high-HDI countries (P < 0.001). Hence, a reduction in anesthesia-related CA rates over time was observed. Both perioperative and anesthesia-related CA rates only decreased with a high-HDI between time periods, and perioperative CA rates during 1990-2017 were 4-fold higher with low-compared to high-HDI in geriatric patients.